Identifying Aquifer Layers Using the Vertical Schlumberger Configuration Resistivity Geoelectric Method in the Permata Hijau Housing Complex, Koya Barat Village, Muara Tami District, Jayapura - Syahardian, Rangga; Mantiri, Steven Y.Y.; Sutarman, Tatang (Jurnal Fisika Papua, 2025)
Research on identifying aquifer layers using the vertical Schlumberger Configuration Resistivity Geoelectric method was carried out in the Permata Hijau Housing Complex, Koya Barat Village, Muara Tami District, Jayapura City. This research aims to determine the resistivity, location and depth of the aquifer layer. The research methods used are field geophysical surveys and geophysical computing. The field geophysical survey method used is the geoelectric method. Field geophysical surveys, using the IREST300f resistivity meter, obtained other data on potential and electric current strength for field resistivity analysis. Computational geophysical methods provide the actual resistivity and vertical profile of soil layers. The number of vertical research points is 5 points. The research results show that there is an aquifer layer at each research point with variations in resistivity values, location and depth. The groundwater aquifer layers are vertical, namely at point 1 there are 2 free aquifer layers with resistivities of 3.34 Ωm and 1.65 Ωm. At point 2 there are 4 layers of unconfined aquifer with resistivities of 9.31 Ωm, 7.13 Ωm, 3.30 Ωm and 6.12 Ωm. At point 3 there are 3 layers of unconfined aquifer with resistivities of 5.61 Ωm, 3.00 Ωm and 1.61 Ωm. At point 4 there are 2 layers of unconfined aquifer with resistivities of 9.30 Ωm and 4.52 Ωm. At point 5 there are 3 unconfined aquifer layers with resistivities of 2.35 Ωm, 8.38 Ωm and 3.18 Ωm. The free aquifer layer is visible at point 1, found in layer 8 with a depth of 4.95-8.80 m and layer 10 with a depth of 19.20-24.00 m. The free aquifer layer is visible at point 2, found in layer 5 with a depth of 3.00-6.80 m and layer 7 with a depth of 16.10-20.00 m. layer 9 with a depth of 8.80-19.20 m and layer 11 6.12 Ωm with a depth of 53.00-76.00 m. The free aquifer layer is visible at point 3, found in Layer 5 with a depth of 3.40-6.00 m; layer 9 with a depth of 15.50-37.30 m; and layer 12 with a depth of 80.00-97.00. The free aquifer layer is visible at point 4, Layer 6 with a depth of 4.28-7.35 m. and Layer 10 with a depth of 50.00-57.40 m. The free aquifer layer is visible at point 5, Layer 4 with a depth of 5.31-5.65 m. Layer 8 has a depth of 15.50-39.00 m and layer 11 has a depth of 93.40-146.00 m.